Criminal Law Reform in Indonesia: Has Been Critical of the New Criminal Code - Murshal Senjaya (PT. Anagata Sembagi Education, 2025)
The criminal law reform in Indonesia is one of the important efforts to answer the challenges of community development and ever-evolving social dynamics. One of the main milestones in this criminal law reform is the ratification of the new Criminal Code (KUHP) which has gone through a long process from the beginning of its drafting to becoming a valid legal product. This study aims to analyze how critical the new Criminal Code is to the need for criminal law that is fair, progressive, and in accordance with democratic values and human rights. Through a qualitative approach, this study explores various aspects of the changes that have taken place in the new Criminal Code, in terms of substance, procedure, and implementation in legal practice. In addition, this study also critically examines whether these changes can address the challenges of modern criminal law, and whether the new Criminal Code is capable of creating a more responsive and inclusive legal system. The results of this study are expected to contribute to a deeper understanding of the relevance of criminal law reform in the context of social and legal change in Indonesia, as well as to serve as evaluation material for policy makers and legal practitioners in implementing a new Criminal Code that is more effective and equitable